Pengaruh Acceptance and Commitment Therapy (ACT) terhadap Gangguan Depresi dan Ansietas Pasien Gagal Ginjal Kronik - Allowda Helena Roselyn Zebua; Ernita Simamora; Yasman Suasono Buulolo; Elis Anggeria (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2025)
Introduction: Patients often suffer from anxiety and depression. Acceptance and attachment therapy is effective in treating depression and anxiety. Chronic kidney failure patients on hemodialysis are more able to accept and advocate for feelings of depression and anxiety when they use this treatment. Purpose: to examine the effect of Acceptance and Commitment Therapy (ACT) on depressive and anxiety disorders in patients with chronic kidney failure.Method: This study used a one group pretest-posttest design. This research was conducted RSU Royal Prima Medan. The population taken was all patients with chronic kidney failure in the hemodialysis room as many as 50 people. The technique used in sampling is nonprobability sampling (purposive sampling), and the number of samples is 50 people. The research instrument for depression and anxiety levels used the Hospital Anxiety and Depression Scale (HADS). Univariate data analysis using frequency tables, and bivariate using the Wilcoxon test.Results: The results of the study found that before the ACT Acceptance and Commitment Therapy (ACT) therapy was carried out, the majority of depressive and high anxiety disorders were 24 patients (48%), after treatment the majority of depression and low anxiety disorders were 28 people (56%). The effect of ACT on depressive and anxiety disorders in chronic kidney failure patients obtained a Z-score -2429 with a p-value of 0.015.Conclusion: It can be concluded that there is an effect of ACT on depressive and anxiety disorders in patients with chronic kidney failure